Financial planner for Z generation lifestyle towards financial freedom - Oktarina, Dian; Arlinda, Rezza; Wulandari, Dewi Ayu; Africa , Laely Aghe; Khalifaturofiah, Sholikha Oktavi (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
The Z generation has high purchasing power and tends to be consumptive. Apart from that z generation also has the characteristic of FOMO (Fear of Missing Out) where they feel they have to follow various existing trends including fashion trends, gadgets and so on which of course will empty their pockets. Fulfillment of consumer behavior and the characteristics of FOMO will certainly have an impact on the increasing number of loans or credit applied for by z generation such as the use of pay later. If done continuously and for a long time, the use of pay later will cause the z generation to experience financial difficulties. Thus, this shows the importance of the knowledge and skills that z generation should have regarding financial management using applications that are easy to use and can be applied independently, namely Excel for Financial Planners. This is facilitated by the existence of training activities related to financial management and also the practice of making a financial planner for each student using Excel for Financial Planners. The results of this training are that every student knows the importance of planning and students can create and design personal finances with the help of the Excel for Financial Planners System.